GENERAL CHARACTERISTICS OF THE STUDY OF CLINICAL HISTORY OF PREGNANT WOMEN WITH HYPERTENSION STATES - Atkhamova, Sh.R; Ravshanova, S.R.; Kurbanov, B.B. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Objective: to study the features of the clinical, obstetric history of women with hypertensive conditions during pregnancy. Materials and methods of the study: 104 pregnant women admitted to inpatient treatment in the II-III trimester, who were divided into three groups: The first group consisted of 43 pregnant women with severe preeclampsia, the second - 33 pregnant women with mild preeclampsia, and the third group - 28 pregnant women diagnosed with moderate gestational hypertension. Results: primiparous and primiparous women were significantly more common in the group with severe preeclampsia and amounted to 45.5%, in contrast to the second (30.3%) and third groups (25.9%). In 39.4% of cases, women in the second group had their second birth, while in the first group this figure was 20.5%, and in the third group 29.6%, respectively. In one case, the woman in the second group had her fifth upcoming birth. In 27.3% of women in the first group, spontaneous miscarriage was noted, in the second in 24.2% of cases, and in the third 25.9%. Conclusions: when analyzing clinical observations, a significant advantage of aggravated obstetric history is noted in the examined women.